2021
DOI: 10.1002/aenm.202100110
|View full text |Cite
|
Sign up to set email alerts
|

Synergized Multimetal Oxides with Amorphous/Crystalline Heterostructure as Efficient Electrocatalysts for Lithium–Oxygen Batteries

Abstract: High theoretical specific energy of rechargeable lithium–oxygen (Li–O2) batteries makes them very promising in the development of long driving range electric vehicles and energy storage on large‐scale. However, the large polarization and poor cycling stability associated with insufficient catalytic cathodes and the insulating nature of discharge products limit their practical applications. Here, the fabrication of a trimetallic CoFeCe oxide with an amorphous/crystalline heterostructure acting as an electrocata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 52 publications
0
38
0
1
Order By: Relevance
“…09‐0355) were collected after discharge at a voltage window 2.35−4.35 V, demonstrating good crystallinity of the discharge products. [ 53 ] The discharge products decomposed completely after charging, and the crystallinity of the SnSe nanosheet changed slightly after 100 cycles. Raman spectroscopy and Fourier transform infrared spectroscopy (FTIR) provide further evidence for the species on the electrode surface.…”
Section: Resultsmentioning
confidence: 99%
“…09‐0355) were collected after discharge at a voltage window 2.35−4.35 V, demonstrating good crystallinity of the discharge products. [ 53 ] The discharge products decomposed completely after charging, and the crystallinity of the SnSe nanosheet changed slightly after 100 cycles. Raman spectroscopy and Fourier transform infrared spectroscopy (FTIR) provide further evidence for the species on the electrode surface.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the addition of Ce when constructing a Fe 2 O 3 –CoO heterojunction resulted in the formation of a CeO 2 buffer layer, which reduced the lattice mismatch and dislocation between the two materials and improved the cyclic stability and capacity of the ternary oxide. [ 193 ] 5) Recent experimental and computational studies have shown that there can be more than one kind of defect at the hetero‐interface at the same time, and each kind of defect can change the state of the interface, thereby affecting the energy storage performance of the transition metal oxide. Thus, future work should focus on maximizing the performance of heterostructure electrodes by manipulating various defects at the interface.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…More importantly, the loosely packed structure is more conducive to buffer volume change and rapid ion transmission during the redox process in the bulk of the phosphide. 18 However, pure amorphous materials often exhibit lower conductivity and toughness than crystalline materials, which limit their individual application. Inspired by these, crystalline bimetallic oxides combined with amorphous phosphides to form a unique amorphous-crystalline structure, which combined with the advantages of high electrical conductivity and high specific capacity of the crystal phase, and with the disordered arrangement of the amorphous phase, which can achieve excellent rate capability and cycling stability.…”
Section: Introductionmentioning
confidence: 99%